Multilevel Analysis on the Social Determinants of Cervical Cancer in Yogyakarta - Heni Elmiani Sari; Ambar Mudigdo; Argyo Demartoto (Masters Program in Public Health, 2016)
Background: There are 527.600 new cases of invasive cervical cancer. Cervical cancer is caused by infection with the Human Papilloma Virus (HPV) 16 and 18 study was conducted in the city of Yogyakarta. This study aimed to analyze the social determinants on cervical cancer by multilevel analysis in Yogyakarta.Subjects and Methods: This was an observational analytic study with case control design. This was conducted on March 31 to May 4, 2016. A total of 120 samples were selected by fixed disease sampling with a ratio 1:3. The data collected was using a questionnaire and analyzed with Logistic Regression.Results: The risk of cervical cancer with a positive effect on family income (OR = 3.45 95% CI = 0.26 to 45.45 p = 0.346), age of first sexual intercourse (OR = 8.54 95% CI = 1.17 to 62.41 p = 0.034), number of sexual partners (OR = 14.60 95% CI = 2.93-72.66 p = 0.001), oral contraceptives (OR = 1.85 95% CI = 0:37 to 9:20 p = 0452), nutritional status (OR = 5.69 95% CI = 1.36 to 23.82 p = 0.017), hygiene genitalia (OR = 9:23 95% CI = 1.76 to 48.35 p = 0.009), and an effect reversed by education (OR = 0:14 95% CI = 0:09 to 2:08, p = 0.155). ICC value of 40.68% indicating the risk of cervical cancer in women varies and a variation of 40.68% at the level of environmental sanitation home.Conclusion: There is a positive effect of family income, age of first sexual intercourse, number of sexual partners, nutritional status, hygiene genitalia, and sanitary home environment, on the risk of cervical cancer. There is an inverse effect of education on the risk of cervical cancer. The society is expected to be aware of cervical cancer.Keywords: multilevel analysis, social determinants, cervical cancer.Correspondence: Heni Elmiani Sari. School of Midwifery (AKBID) Kutai Husada, Tenggarong, Indonesia. Email: henyelmiani@gmail.comJournal of Epidemiology and Public Health (2016), 1(2): 100-107https://doi.org/10.26911/jepublichealth.2016.01.02.03